Resuscitation attempts and duration in traumatic out-of-hospital cardiac arrest - Beck, B.; Bray, Janet; Cameron, P.; Straney, L.; Andrew, E.; Bernard, S.; Smith, K. (Elsevier, 2017)
Background This study aimed to understand factors associated with paramedics’ decision to attempt resuscitation in traumatic out-of-hospital cardiac arrest (OHCA) and to characterise resuscitation attempts =10 min in patients who die at the scene. Methods The Victorian Ambulance Cardiac Arrest Registry (VACAR) was used to identify all cases of traumatic OHCA between July 2008 and June 2014. We excluded cases <16 years of age or with a mechanism of hanging or drowning. Results Of the 2334 cases of traumatic OHCA, resuscitation was attempted in 28% of cases and this rate remained steady over time (p = 0.10). Multivariable logistic regression revealed that the arresting rhythm [shockable (adjusted odds ratio (AOR) = 18.52, 95% confidence interval (CI):6.68–51.36) or pulseless electrical activity (AOR = 12.58, 95%CI:9.06–17.45) relative to asystole] and mechanism of injury [motorcycle collision (AOR = 2.49, 95%CI:1.60–3.86), fall (AOR = 1.91, 95%CI:1.17–3.11) and shooting/stabbing (AOR = 2.25, 95%CI:1.17–4.31) relative to a motor vehicle collision] were positively associated with attempted resuscitation. Arrests occurring in rural regions had a significantly lower odds of attempted resuscitation relative to those in urban regions (AOR = 0.64, 95%CI:0.46–0.90). Resuscitation attempts =10 min represented 34% of cases in which resuscitation was attempted but the patient died at the scene. When these resuscitation attempts were selectively excluded from the overall EMS treated population, survival to hospital discharge non-significantly increased from 3.8% to 5.0% (p = 0.314). Conclusion Survival in our study was consistent with existing literature, however the large proportion of cases with resuscitation attempts =10 min may under-represent survival in those patients that receive full resuscitation attempts.